The transition process in Eastern Europe: European security policy redefined - Kai Hirschmann (Intereconomics, 1995)
Traditional views of security policy have focused almost exclusively on defence and military topics. The process of transition in eastern Europe makes it necessary to take a much broader approach in which, for example, areas such as economic and social policy, or world trade and monetary relations, are included.
Keywords: 330